European neighbourhood policy and economic reforms in the eastern neighbourhood - Wojciech Paczyński (Center for Social and Economic Research (CASE), 2009)
The paper discusses the current and potential role of the European Neighbourhood Policy (ENP) in anchoring economic reforms in the countries of the EU's Eastern Neighbourhood. It claims that it is too early to assess the success of the ENP in this sphere especially given that the actual progress of the ENP agenda has been limited. A review of the empirical evidence on external reform anchors confirms that the ENP shares some features with the EU accession process that has proven to be an effective mechanism supporting major economic, political and social changes in the countries concerned. The eventual ENP economic offer is meaningful and integration with the EU is getting stronger public support in several CIS countries and among their political elites. On the other hand several factors limit the reform anchoring potential of the ENP. This paper offers recommendations on policies that could strengthen this potential.
Keywords: P16; P48; Y80; Z13; 330; ENP; CIS; EU; political economy; economic reforms; reform anchoring; EU-Nachbarstaaten; Politische Reform; Wirtschaftsreform; GUS-Staaten